All Days 2014
DOI: 10.4043/24961-ms
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Hydrate Inhibition Performance of MEG in Under-Inhibition System: Reduction Opportunities of MEG Injection for Offshore Gas Field Developments

Abstract: In offshore gas field development, mono-ethylene glycol (MEG) has been a robust choice for hydrate inhibition in subsea production systems and flowlines. Once hydrate blockage forms, considerable efforts and loss of production are inevitable to remediate the hydrate blockage. Therefore, the industry has been relying on the injection of considerable amount of MEG which is used to be over-estimated based on the worst operation condition: shut-in pressure, sea water temperature, and maximum water cut. However, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Low-dosage hydrate inhibitors (LDHIs), such as kinetic hydrate inhibitors (KHIs), are becoming more widespread because they can be used at very low dosages (less than 5 wt % of the aqueous phase) . This compares to conventional thermodynamic hydrate inhibitors (THIs) that often need to be dosed in very large amounts (up to 50 wt % or more of the produced water). ,, The KHIs have also, in many cases, been used together with THIs to decrease the large amounts of chemicals needed to obtain sufficient inhibition. , …”
Section: Introductionmentioning
confidence: 99%
“…Low-dosage hydrate inhibitors (LDHIs), such as kinetic hydrate inhibitors (KHIs), are becoming more widespread because they can be used at very low dosages (less than 5 wt % of the aqueous phase) . This compares to conventional thermodynamic hydrate inhibitors (THIs) that often need to be dosed in very large amounts (up to 50 wt % or more of the produced water). ,, The KHIs have also, in many cases, been used together with THIs to decrease the large amounts of chemicals needed to obtain sufficient inhibition. , …”
Section: Introductionmentioning
confidence: 99%
“…Before the hydrate performance test was conducted, the solutions of Table were further diluted with deionized water as shown in Table to reflect the solution average concentration after the injection points during gas transportation. Typically, injected lean MEG concentration is 90 wt %, but it can get diluted to below 40 wt % inside the pipeline with water produced from the wells. ,, …”
Section: Experimental Methodologymentioning
confidence: 99%
“…Mike Hodder's (Shin et al, 2014) research has found that the most effective way to combat the hydrate is to add salt and other chemical inhibitors that can reduce the water's activity. Kim Jakyung (Kim et al, 2011) studied the inhibition of monoethylene glycol (MEG) with polyethylene caprolactam (PVCap) to delay the formation of hydrate and prevent the agglomeration of hydrate particles. Kawamura (Makogon and Cieslesicz, 1981) has studied the hydrate decomposition caused by the injection of MA and found that the concentration of hydrate surface inhibitors varies.…”
Section: Introductionmentioning
confidence: 99%